Кулики (Aves, Charadriiformes) Северного Кавказа. Сообщение I - Казаков, Б.А.; Белик, В.П.; Пекло, А.М.; Тильба, П.А. (Вестник зоологии, 1981)
The first part of the faunistic review of Charadriiformes of the North Caucasus includes a description of 10 species. Burhinus oedicnemus, Charadrius dubius, Ch. alexanarinus, Ch. asiaticus, Eudromias morinellus Vanellus vanellus nest there. Pluvialis squatarola. P. apricaria. Charadrius hiaticula, Chettusia gregaria are migrants. The evidence are generalized on distribution, quantity, periods of migration and reproduction.